The golden rule in sports : investing in the conditions of cooperation for a mutual advantage in sports competitions - Bockel, Alicia (Springer Fachmedien Wiesbaden Imprint: Springer VS, 2015)
Elite level sport lends itself to a highly competitive environment that encourages players to seek a competitive advantage in order to win. Since competition is an inherent condition that is also considered desirable in this setting, it may at first glance seem as if cooperation does not have any room in elite level sports. Sustainable cooperation can be mutually advantageous for players, but it only has a chance of coming into fruition if it is also in line with individual players' self-interests. In order for morality and self-interests to align with one another, investment in the conditions is required. Alicia Bockel analyzes ways that players can invest in the conditions of sustainable cooperation for a mutual advantage despite a highly competitive sports environment. Contents Cooperation for Mutual Advantage Conditions of Cooperation Investment in the Conditions Target Groups Researchers, students, and teachers of sports ethics, economics, and business ethics. Practitioners and governing bodies in sports, athletes, and sport fans.  The Author Dr. Alicia Bockel is a PhD graduate of HHL Leipzig Graduate School of Management, holds an MBA in Strategic Management from Sacred Heart University, and a B.A. in Religion and Psychology from Saint Leo University.